Associations between diurnal preference, impulsivity and substance use in a young-adult student sample. (2nd January 2021) - Evans, Simon L.; Norbury, Ray
ABSTRACT: A diurnal preference for eveningness is common in young adulthood and previous research has associated eveningness with anxiety symptoms as well as increased smoking and alcohol use behaviors. There is some evidence that impulsivity might be an important explanatory variable in these associations, but this has not been comprehensively researched. Here we used both subjective and objective measures of impulsivity to characterize impulsive tendencies in young adults and investigated whether trait impulsivity or trait anxiety could mediate the link between eveningness and substance use. A total of 191 university students (169 females), age range 18–25 y, completed the study. Diurnal preference, sleep quality, anxiety, impulsivity, and substance use were assessed by questionnaire. Impulsivity was also measured using a delay discounting task. Eveningness correlated with trait anxiety and trait impulsivity, and these associations were still significant after controlling for sleep quality. On the delayed discounting task, eveningness correlated with a tendency to prefer smaller immediate rewards over delayed, larger ones. Evening types also reported higher levels of alcohol and cigarette use even after controlling for sleep quality. These associations were found to be completely mediated by self-reported impulsivity; anxiety did not contribute. The current results could help inform interventions aiming to reduce substance use in young adult populations.